2020
DOI: 10.33437/ksusbd.555770
|View full text |Cite
|
Sign up to set email alerts
|

Altıncı Sınıf Tam Sayılar Konusunda Uygulanan Gerçekçi Matematik Eğitiminin Öğrencilerin Matematik Motivasyonlarına Etkisi

Abstract: öğrencilerin matematik motivasyonu sontest puanları üzerinde kontrol grubundaki öğrencilerin matematik motivasyonu sontest puanlarına kıyasla daha etkili olmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…After detecting the difficulties and misconceptions of students when they have operations with integers, it is seen that teachers and researchers have tried various teaching methods or materials as a solution to this situation (Fuadiah, Suryadi, & Turmudi, 2017). Performing activities on problem posing by associating information about integers with daily life can be applied as one of the teaching methods that will contribute to students' understanding of integers more easily (Berkant & Yaren, 2020). Since it is recommended to use examples such as profit-loss, debit-credit, elevator, thermometer from daily life during the teaching of integers in the curriculum of the mathematics course, which was reorganized in 2018, it is believed that doing problem-posing activities by making use of these examples related to integers will be more successful in learning integers.…”
Section: Why Are Integers Important?mentioning
confidence: 99%
“…After detecting the difficulties and misconceptions of students when they have operations with integers, it is seen that teachers and researchers have tried various teaching methods or materials as a solution to this situation (Fuadiah, Suryadi, & Turmudi, 2017). Performing activities on problem posing by associating information about integers with daily life can be applied as one of the teaching methods that will contribute to students' understanding of integers more easily (Berkant & Yaren, 2020). Since it is recommended to use examples such as profit-loss, debit-credit, elevator, thermometer from daily life during the teaching of integers in the curriculum of the mathematics course, which was reorganized in 2018, it is believed that doing problem-posing activities by making use of these examples related to integers will be more successful in learning integers.…”
Section: Why Are Integers Important?mentioning
confidence: 99%
“…Studies conducted in our country (Bintaş, Altun & Arslan, 2003;Çakır, 2013;Çilingir, 2015;Demirdöğen, 2007;Demirdöğen & Kaçar, 2010;Ersoy, 2013;Özdemir & Üzel, 2011;Üzel, 2007;Yazgan, 2007;Korkmaz & Tutak, 2017;Erdoğan, 2018) reveal that there are studies investigating the effect of the RME approach on student achievement. In addition, there are also studies examining the effect of the RME approach on student motivation, attitudes, and thoughts (Berkant & Yaren, 2018;Kurt & Doğan, 2019). When the studies are examined; It has been observed that there are limited studies on the RME approach on geometry (Korkmaz & Tutak, 2017;Çelik, 2016;Deniz & Uygur-Kabael, 2017;Kurt & Doğan, 2019).…”
Section: Horizontal Mathematizationmentioning
confidence: 99%
“…Within the scope of all these sub-learning areas, it was observed that several studies were conducted on various topics such as natural numbers and operations with natural numbers (Albayrak et al, 2019;Ercive & Narlı, 2019;Paydar & Doğan, 2021;Tuluk & Akyüz, 2019), fractions and operations with fractions (Altıparmak & Palabıyık, 2019;Topçu & Gürefe 2020;Özer et al, 2020), decimal notations Karataş et al, 2021), rates (Erdem et al, 2018;Yapıcı & Altay, 2017), multipliers and multiples (Karakuş & Yeşilpınar, 2018), sets (Biber & Tuna, 2016;Yücesan, 2011), integers and operations with integers (Berkant & Yaren, 2020;Bozkurt & Polat, 2011;Erdem et al, 2015;Kiraz & Cemalettin, 2020;Şengül & Zengin, 2015), rational numbers and operations with rational numbers (Altun & Çelik, 2018;Gürbüz & Birgin, 2008;Macit & Nacar, 2019;Yenilmez & Yıldız, 2018), ratio and proportion (Deveci, 2021;Güler & Didiş Kabar, 2017;Şengül & Erdoğan, 2017), exponential expressions (Eymen & Duatepe Paksu, 2015;Eymen İkizoğlu & Duatepe Paksu, 2016;Güzel & Yılmaz, 2020) and rooted expressions (Aksu et al, 2013;Aydoğdu, 2020;Toluk Uçar, 2015). In these studies, it was found that the students had deficiencies in reading and writing the numbers, grouping numbers and writing the groups according to their digits after grouping the numbers or they over and under-used the 0 concepts (Albayrak et al, 2019), tended to do different types of errors such as not being able to establish the part-whole relationship in problem posing for operations with fractions, attribute natural number meaning to fraction dimensions, have an inability to ...…”
Section: Introductionmentioning
confidence: 99%